Family Empowerment Intervention Model through Family Class in Decision-Making during Maternal Emergencies: A Scoping Review - Juariah Juariah; Tris Eryando (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Maternal mortality remains a persistent global health challenge, reflecting inequalities in access to and quality of obstetric care. Most maternal deaths occur due to delays in decision making during obstetric emergencies at the household level. Family members, particularly husbands and close relatives, play a central role in determining referral actions. Empowering families through the family class approach has the potential to enhance their preparedness in recognizing danger signs and making timely decisions during critical maternal conditions. Objective : This scoping review aims to map existing literature on factors influencing decision making during maternal emergencies and to identify family empowerment intervention models— particularly through the family class approach—that contribute to improving maternal outcomes and reducing the risk of maternal mortality Research Methods/ Implementation Methods : This study employed a scoping review design based on the Arksey and O’Malley framework and followed the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) guidelines. Literature searches were conducted in PubMed, Scopus, and Google Scholar databases using the keywords maternal mortality, family empowerment, decision-making, emergency obstetric care, and family class, covering studies published between 2010 and 2025. Eligible articles were thematically analyzed to identify determinants and forms of family empowerment interventions in maternal emergency decision-making. Results : A total of 27 articles met the inclusion criteria. The findings indicate that family class interventions improve knowledge, early danger sign detection, and communication between families and healthcare providers. These interventions accelerate decision-making and reduce delays in seeking care. However, most studies were short-term and lacked evaluation of their long-term effectiveness in reducing maternal mortality rates. Conclusion/Lesson Learned : he family class model represents a promising family empowerment strategy to strengthen decision-making capacity during maternal emergencies. Integration of this approach into community-based maternal and child health programs, supported by cross-sector policies, is strongly recommended. Further longitudinal studies are needed to assess its long-term impact and applicability across diverse cultural settings.